Spain’s party system development trends in the context of the electoral cycle 2019 - A. Baranov (Ибероамериканские тетради, 2019)
The topicality of the article is that the party system of Spain is undergoing serious transformations, the positioning of political forces and their ideologies, the organizational structure are changing significantly. National parliamentary elections are held for the fourth time in 4 years, which is unique to the countries of consolidated democracy. Trends in the development of Spain are relevant for cross- national comparisons of party systems. Methods – systems approach, synchronous comparative analysis, a secondary analysis of the results of opinion polls, mapping of party support in the elections. Materials: regulations; statements by party leaders; pre-election programs; results of sociological surveys; statistics on the results of elections. Results: The crisis of the party system in Spain is peculiar to the transition from a bipartisan model to a model of moderate pluralism, increased fragmentation, significant volatility, and the dependence of the main national parties on the support of regional parties. In the electoral cycle of 2019, the party system of Spain is a system of moderate pluralism (5 leading actors) with the growing role of regional parties, pragmatic coalitions are inevitable for creating a government. The economic recovery of 2014–2019 influenced the decline in the influence of “Unidos Podemos”, their electorate partially returned to the PSOE. In European and subnational elections, these trends are even more pronounced due to the format of electoral systems and the isolation of regional party systems. The threefold structure of the Spanish electorate, distributed mainly among left-leaning centers, center-right and regional nationalists, is preserved. An analysis of the statistical results of the elections and questionnaires proves an inversely correlated relationship between the level of support for the PSOE and “Unidos Podemos” in the center-left segment, and the level of support for the People’s Party, “Citizens” and “Vox” in the center-right camp. The influence of parties is extremely uneven across autonomous communities, and unevenness is increasing. The increase in the instability of the party system in Spain is predicted due to the growing influence of new parties and the underdeveloped culture of parliamentary coalitions. This process increases the chances of Catalan nationalists. A radical reform of the political system of Spain is brewing; the electorate of the left parties expresses the greatest demand for reform.